К экологии малоизвестных видов полужесткокрылых (Heteroptera) Европейской части СССР. Сообщение III - Пучков, В.Г. (Вестник зоологии, 1967)
Some ecological observations were made during the expeditions to the South of the European part of the USSR (1961-1966). On the basis of these observations a brief characteristic is given of the life peculiarities of 24 Heteroptera species, the majority of which are new for the fauna of the South Ukraine or the whole Soviet Union.